Uma Leitura de Mão Dupla: Leituras e Influências na Poesia de João Cabral de Melo Neto - Santos, Elis Denise Lélis dos (2008)
The goal of our work is to investigate the influences reading from the poet Joao Cabral de Melo Neto and possible overruns through the conquest of a unique style. Contextualizaremos the production of literary and intellectual author, working with the "field", "context" and "paratopia" based on readings of The rules of art (1996), Pierre Bourdieu and The context of literary work (2001), Dominique Maingueneau, respectively. Abordaremos the influences received by the poet in the literature and other fields such as visual arts, architecture, mathematics, philosophy and the different places where resided and the travel he has done. Use the categories "influence" and "overrun", systematized by the American literary critic Harold Bloom works in The anguish of influence (1991) and A map of desleitura (2003). So with the idea of overcoming, we want to examine The work Education by stone (1966) which marks the poetry of John Cabral a more mature by their experiences with the language. First, we will see the context of production in prose and verse of the author. Then mapeamos their influences, and a third time, investigate how the poet surpassed, building an individual and own poetic.